Profitability and Company Value: Empirical Study of Manufacture Companies in Indonesia Period 2009 - 2014 - Lestari, Siti Ayu; Armayah, Mursalim (Information Management and Business Review, 2016)
Maximizing the value of the company is one of the financial issues are interesting to study. Profitability is one of the factors that influence value of enterprise be in accordance with asset and equity owned. The purpose of this research is to describe the correlation between profitability and company value. Based on the problem and purpose research, the research is designed as quantitative research. Secondary data used as the basis for the analysis was obtained from ICMD with observation period of 5 years to 10 companies. Data analyzed by using linear regression multiple analyses. Empirical results show that profitability variability explains change of company value. Return on Investment and Return on Equity has positive and significant effect on company value, but Net Profit Margin negatively and significantly affects company value.